Ethnographier la violence dans la prostitution : effets du contexte, effets du terrain et force des émotions - Mayer, Sibylla (Parcours antrhopologiques, 2016)
Dans cet article, je prends pour objet une enquête passée, menée sur la prostitution de rue. Partant du vécu d’une émotion forte en aval de la recherche, après la sortie du terrain et après la discussion des résultats, je m’interroge sur la place des émotions dans l’enquête, en particulier en lien avec l’ethnographie de la violence dans la prostitution. En revenant sur le meurtre d’une personne connue sur le terrain et sur ce que cet événement a suscité en termes de retour sur ma démarche, je montre notamment que les émotions agissent en modifiant notre vécu, y compris en aval du terrain, nous permettant de revenir sur notre positionnement face à l’objet de recherche.
https://journals.openedition.org/pa/495
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; discipline; ethnographie; europe; luxembourg; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; travail du sexe; violences; émotions

Gendered fields: Women, men, and ethnography - Karim, Wazir-Jahan Begum; Bell, Diane; Caplan, Pat (Routledge, 2013)
Examines and explores the progress of feminist anthropology, the gendered nature of fieldwork itself, and the articulation of gender with other aspects of the persona of the ethnographer.
Keywords: anthropologie; approches et analyses; discipline; ethnographie; genre; outils; ouvrages de références; point de vue situé; sciences humaines

Orientalisme, occidentalisme et contrôle des femmes - Nader, Laura; Armengaud, Françoise (Nouvelles Questions Féministes, 2006)
L’autrice part du concept d’« orientalisme » tel qu’il a été élaboré par Edward Saïd pour montrer que ce processus « d’altérisation » mené par l’Occident doit être mis en parallèle avec un processus symétrique, mené par les pays arabo-musulmans et qu’elle nomme « Occidentalisme ». En effet, chacun de ces grands ensembles politiques se sert du principe du respect des femmes pour plaider sa supériorité culturelle par rapport à l’autre. Dans les deux configurations, ce principe vise par ailleurs d’autres finalités : celle de convaincre « ses propres » femmes des avantages que leur octroie le système d’oppression dans lequel elles se trouvent insérées. Dans le cas de l’Occident, le crédit accordé à sa « position de supériorité » est encore renforcé par l’idéologie du progrès par le développement, un discours qui présuppose que la situation des femmes ne peut que s’améliorer avec l’avancement techno-économique d’une société.
Keywords: anthropologie; approches et analyses; cours; discipline; femmes* arabes; femmes* occidentales; histoire et politique; identité des femmes*; intersectionnalité; justice sociale; monde arabe; occident; patriarcat; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; systèmes d'oppressions; thématiques

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences